Clinical and Economic Outcomes of Erythropoiesis-Stimulating Agent Hyporesponsiveness in the Post-Bundling EraPlain-Language Summary - Borut Cizman; Helen T. Smith; Rodrigo Refoios Camejo; Linda Casillas; Harjeet Dhillon; Fan Mu; Eric Wu; Jipan Xie; Peter Zuckerman; Daniel Coyne (Kidney Medicine, 2020)
Rationale & Objective: Since the change in erythropoiesis-stimulating agent (ESA) labeling and bundling of dialysis services in the United States, few studies have addressed the clinical importance of ESA hyporesponsiveness and none have considered health care resource use in this population. We aimed to further explore ESA hyporesponsiveness and its consequences. Study Design: Retrospective observational cohort study. Setting & Participants: US Renal Data System Medicare participants receiving dialysis with a minimum 6 months of continuous ESA use from 2012 to 2014. Predictors: Erythropoietin resistance index (≥2.0 U/kg/wk/g/L) and ESA dose were used to identify ESA hyporesponders and hyporesponsive subgroups: isolated, intermittent, and chronic. Outcomes: Associations between ESA responsiveness and mortality, cardiovascular hospitalization rates, and health care resource use were evaluated and compared across subgroups. Analytical Approach: Baseline characteristics were compared using Wilcoxon rank sum tests for continuous variables and χ2 tests for categorical variables. Incidence rates of health care resource use were modeled using an unadjusted and adjusted generalized linear model. Results: Of 834,115 dialysis patients in the CROWNWeb database, 38,891 ESA hyporesponders and 59,412 normoresponders met all inclusion criteria. Compared with normoresponders, hyporesponders were younger women, weighed less, and had longer durations of dialysis (all P < 0.001). Hyporesponders received 3.8-fold higher ESA doses (mean, 94,831 U/mo) and erythropoietin resistance index was almost 5 times higher than in normoresponders. Hyporesponders had lower hemoglobin levels and parathyroid hormone levels > 800 pg/mL, and iron deficiency was present in 26.5% versus 10.9% in normoresponders. One-year mortality was higher among hypo- compared with normoresponders (25.3% vs 22.6%). Hyporesponders also had significantly higher rates of hospitalization for cardiovascular events, emergency department visits, inpatient stays, home health agency visits, skilled nursing facility, and hospice days. Limitations: Only US Medicare patients were included and different hyporesponder definitions may have influenced the results. Conclusions: This study explored ESA hyporesponsiveness using new definitions and incorporated clinical and economic outcomes. It established that ESA-hyporesponsive dialysis patients had higher mortality, cardiovascular hospitalization rates, and health care costs as compared with ESA-normoresponsive patients.